The HD-Zip transcription factor GhHB12 represses plant height by regulating the auxin signaling in cotton - Yan LIU; Wei-ping WANG; Lin ZHANG; Long-fu ZHU; Xian-long ZHANG; Xin HE (Journal of Integrative Agriculture, 2023)
Upland cotton (Gossypium hirsutum L.) is the most important natural textile fiber crop worldwide. Plant height (PH) is a significant component of plant architecture, strongly influencing crop cultivation patterns, overall yield, and economic coefficient. However, cotton genes regulating plant height have not been fully identified. Previously, an HD-Zip gene (GhHB12) was isolated and characterized in cotton, which regulates the abiotic and biotic stress responses and the growth and development processes. In this study, we showed that GhHB12 was induced by auxin. Moreover, overexpression of GhHB12 induces the expression of HY5, ATH1, and HAT4, represses the spatial-temporal distribution, polar transport, and signaling of auxin, alters the expression of genes involved in cell wall expansion, and restrains the plant height in cotton. These results suggest a role of GhHB12 in regulating cotton plant height, which could be achieved by affecting the auxin signaling and cell wall expansion.